Donepezil + chromone + melatonin hybrids as promising agents for Alzheimer's disease therapy. (1st January 2019) - Pachón-Angona, Irene; Refouvelet, Bernard; Andrýs, Rudolf; Martin, Helène; Luzet, Vincent; Iriepa, Isabel; Moraleda, Ignacio; Diez-Iriepa, Daniel; Oset-Gasque, María-Jesús; Marco-Contelles, José; Musilek, Kamil; Ismaili, Lhassane
Abstract: We describe herein the design, multicomponent synthesis and biological studies of new donepezil + chromone + melatonin hybrids as potential agents for Alzheimer's disease (AD) therapy. We have identified compound 14n as promising multitarget small molecule showing strong BuChE inhibition (IC50 = 11.90 ± 0.05 nM), moderate hAChE (IC50 = 1.73 ± 0.34 μM), hMAO A (IC50 = 2.78 ± 0.12 μM), and MAO B (IC50 = 21.29 ± 3.85 μM) inhibition, while keeping a strong antioxidant power (3.04 TE, ORAC test). Consequently, the results reported here support the development of new multitarget Donepezil + Chromone + Melatonin hybrids, such as compound 14n, as a potential drug for AD patients cure. Graphical Abstract: